Користење на генерациските разлики како основа за разбирање на работното место - Јанеска илиев, Александра; Миладинова, Бранкица (Економскиот факултет во Скопје, 2021)
As diversity in age increases in the workforce, the newer generations are shifting values thus creating a new working environment. With many Generation Y members already in the workforce, managers are likely to be required to deal with the generational differences that appear to exist among employees. In our research effort, we aimed at discovering what the new generation will bring and how it will affect work life. Our main struggle is to find out whether the various generational groups differ in the context of work centrality on one hand and how this impacts work engagement on the other, with a specific focus on generation Z. For this paper, a sample of 204 respondents was gathered including various generational groups aged between 19 and 48 years. The questionnaire was made up of 3 different sections. Section A focused on the emographic information. Section B is related to work centrality, suggested by the Work Centrality Scale. Section C concentrated on work and well-being using the Utrecht Work Engagement Scale. The results implicated the existence of a significant correlation between age and work engagement, as well as work centrality and work engagement.
Keywords: generation gap, work-life balance, work centrality, well-being